Handling challenging questions in the management of chronic myeloid leukemia: when is it safe to stop tyrosine kinase inhibitors? - Rea, Delphine (Blood Adv, 2020)
The paradigm for managing patients with chronic myeloid leukemia is evolving. In the recent past, restoring a normal life expectancy while patients are receiving never-ending targeted therapy with BCR–ABL1 tyrosine kinase inhibitors through prevention of progression to blast phase and mitigation of iatrogenic risks was considered the best achievable outcome. Now, long-term treatment-free remission with continued response off tyrosine kinase inhibitor therapy is recognized as the most optimal benefit of treatment. Indeed, numerous independent clinical trials provided solid proof that tyrosine kinase inhibitor discontinuation was feasible in patients with deep and sustained molecular responses. This article discusses when tyrosine kinase inhibitors may be safely stopped in clinical practice on the basis of the best and latest available evidence.